Extremism: A Social Analysis of the Factors Causing the Emergence of Extremism - Hakima, Boulacheb (Journal of Ecohumanism, 2026)
Extremism is an ideological and behavioral phenomenon through which individuals and groups adopt ideas and beliefs that go beyond the bounds of moderation in thought and practice. Extremism manifests itself when an individual or group rigidly adheres to certain views and beliefs while rejecting opposing viewpoints. Extremism is often based on a rejection of dialogue, discussion, and coexistence with those who are different. Sociologically speaking, an extremist personality is a pattern of thought and behavior that takes shape within a specific social context and is influenced by environmental and cultural factors; it is a personality that feels socially excluded, marginalized, and poorly integrated into society. Psychologically, extremism is understood as a pattern of thought and behavior linked to psychological mechanisms that make the individual more susceptible to adopting radical and exclusionary ideas. Extremism manifests in various forms,it may be ideological, religious, political, or social .and therefore combating it requires joint efforts from all sectors, including educational institutions, the media, and the family, with the aim of fostering a culture of dialogue to reduce the tendency to be drawn into extremist ideas. Accordingly, this article aims to provide a sociological analysis of the phenomenon of extremism by highlighting the social and psychological factors that contribute to individuals joining extremist groups, as well as identifying ways to prevent it.